Academic engagement and academic self-efficacy as predictors of academic procrastination in Peruvian adolescents - Cutipa-Flores, Tito; Fabian-Osorio, Lizvell; Navarro-Cárdenas, Marco Antonio; Abanto-Ramírez, Carlos D. (Frontiers in Education, 2025)
IntroductionAcademic procrastination is a maladaptive learning behavior that can impair student performance. The research aims to determine whether academic engagement and self-efficacy predict academic procrastination in Peruvian adolescents.MethodThis is a cross-sectional predictive design, with a sample of 450 high school students of all grades, selected by convenience. The students were mostly female (60.9%), were in the first year of high school (28.9%) and were from private institutions (85.1%). The averages, variability and distribution of the data obtained were calculated. A correlation analysis was performed between the variables, as well as a multiple correlation analysis and, finally, a multiple linear regression analysis.ResultsThe results showed that self-efficacy was inversely related to academic procrastination (r = −0.250; p < 0.001) and this, in turn, to commitment (r = −0.263; p < 0.005). Self-efficacy was directly related to engagement (r = 0.112; p < 0.005). Self-efficacy (β = −0.223; p < 0.001) and engagement (β = −0.238; p < 0.001) inversely influenced procrastination, explaining 11.8% of its variability (R = 0.344, R2 = 0.118, F = 30.0, p < 0.001).DiscussionThe results showed the importance of academic engagement and self-efficacy in mitigating the propensity for academic procrastination among Peruvian adolescents. Consequently, educational institutions and schools should prioritize the implementation of teaching methodologies and interventions that improve students’ motivation and engagement, as well as foster confidence in their abilities to achieve academic success, in order to counteract the detrimental effects of procrastination on their academic development.